Characterization Of Green Composites Films From Agar As A Potential Packaging Material - Ismail, Nor Azlina (2022)
Agar is a biopolymer extracted from certain red algae. The transparent film made from agar gum is becoming a common and renewable alternative for plastic-based food packaging materials. Agar have speciality in properties such as, high gel strength at low concentration, low viscocity and riversible process.. However, the film produced has poor properties such as brittle, high moisture permeability, and poor thermal stability. Hence the effect on addition of four types of plasticizers (Glycerol, PEG 200, PEG 1000 dan PEG 2000) with variation (10, 20,30 and 40%) has been done. Based on the results obtained, the plasticizing agent PEG 1000 at an addition of 40% was selected for the study of addition of crosslinking agents namely calcium chloride and acrylic resin. To reduce the hydrophilicity properties of agar composites based film, the addition of 40% (w/w) acrylic, whereas the film with the addition of 2% CaCl2 and an immersion time of 4 minutes showed a tensile strength of 57.54 MPa and a breaking point elongation of 1.20%. The agar film with the addition of 1000 PEG 40% showed a tensile strength of 29.02 MPa and a breaking point elongation of 3.19%. This indicates that the addition of acrylic resin as a cross linking agent not only reduces the hydrophilic properties of the film in order to increase the tensile strength. However, the break point elongation results showed a decrease after the addition of acrylic resin. From the infrared diffraction analysis (FTIR) proved the presence of acrylic resin in the film produced with the presence of a peak of 1728.32 cm-1 explains the existence of carbonyl group (C = O).